Traumatic Events, Personality and Psychopathology in Takotsubo Syndrome: A Systematic Review - Galli, Federica; Bursi, Francesca; Carugo, Stefano (Frontiers in Psychology, 2019)
Objective. Tako-Tsubo syndrome (TTS) is historically related to the occurrence of psychological (emotional) factors (“broken heart” syndrome). Our aim was conducting a systematic review analyzing the role of psychological factors in TTS. Methods: All studies on TTS and psychological factors from 1991 to April 2019 were scrutinized according to the Cochrane Collaboration and the PRISMA statement. Selected studies were additionally evaluated for the Risk of Bias according to the Newcastle-Ottawa Scale (NOS). Results. Fifteen case-control studies (Mayo Clinic criteria) were finally selected. Most studies analysed the role of stressful life-events or trauma, although with conflicting findings, while a likely role for long-lasting psychological distress seems to be a homogenous result. Among life-time psychopathology, only anxiety seems to have a significant role. Some studies outlined a likely role for personality, but findings are conflicting. Conclusion. A role for psychological factors in TTS requires more studies with stronger research methodology than the existing ones.